Razvoj gradova u Bosni i Hercegovini / Urban Development in Bosnia and Herzegovina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
The city is the nucleus of Europe and the focus of its economic, political, economic and cultural processes, with the development of urban forms being monitored through the agrarian, industrial and information period. For the purposes of this paper, different approaches to the notion of the city were used, with an emphasis on functional materiality. Due to the ambitious time frame, authors stopped at identifying contemporary tendencies and their repercussions on urban development. Segmenting time into the most important periods for the development of cities, the influence of Eastern and Western civilization on the composition of urbanization ofBosnia and Herzegovina is observed, as well as the influence of contemporary tendencies on configuration at the time of re-municipalization. Following theestablished matrix, an insight into the development of bastards in Bosnia and Herzegovina is provided and whether the research unit follows European trends is analyzed.
Keywords: city; urbanization; globalization; Europeanization; cities in BiH